2016
DOI: 10.1016/j.brainresbull.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of resveratrol suppress the nociceptive neuronal activity of spinal trigeminal nucleus caudalis in rats

Abstract: Although a modulatory role has been reported for the red wine polyphenol resveratrol on several types of ion channels and excitatory synaptic transmission in the nervous system, the acute effects of resveratrol in vivo, particularly on nociceptive transmission of the trigeminal system, remain to be determined. The aim of the present study was to investigate whether acute intravenous resveratrol administration to rats attenuates the excitability of wide dynamic range (WDR) spinal trigeminal nucleus caudalis (Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…These SpVc neurons responded to non-noxious and noxious mechanical stimulation and exhibited a somatic receptive field in the orofacial area (mainly the whisker pad; Fig. 1A), as described previously (Takeda et al, 2000(Takeda et al, , 2012Takehana et al, 2016). In addition, all these neurons responded to mechanical stimulation of the receptive field innervated by ophthalmic and maxillary branches.…”
Section: Activity Of Spvc Wdr Neurons Innervating the Facial Skinmentioning
confidence: 73%
See 4 more Smart Citations
“…These SpVc neurons responded to non-noxious and noxious mechanical stimulation and exhibited a somatic receptive field in the orofacial area (mainly the whisker pad; Fig. 1A), as described previously (Takeda et al, 2000(Takeda et al, , 2012Takehana et al, 2016). In addition, all these neurons responded to mechanical stimulation of the receptive field innervated by ophthalmic and maxillary branches.…”
Section: Activity Of Spvc Wdr Neurons Innervating the Facial Skinmentioning
confidence: 73%
“…Because previous studies have demonstrated that WDR neurons in the SpVc region have an important role in the mechanism underlying hyperalgesia and referred pain associated with orofacial pain (Takeda et al, 2000(Takeda et al, , 2005(Takeda et al, , 2012Nishikawa et al, 2004) and that the discharge of these neurons is suppressed by intravenous resveratrol administration (Takehana et al, 2016), the focus of the present study was on the effects of resveratrol on SpVc WDR neuronal activity; we did not examine nociceptive-specific neurons. Post-stimulus histograms (bin = 100 ms) were generated in response to each stimulus.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 3 more Smart Citations